PELATIHAN AKUNTANSI PERSEDIAAN DAN PERHITUNGAN HARGA POKOK PERSEDIAAN DI PANTI ASUHAN ASIH LESTARI - Dermawan, Elizabeth Sugiarto; Cicilia, Orlin; Amanda, Hanifa Dhiyaa (Jurnal Serina Abdimas, 2023)
The background of this PKM begins with the awareness of the importance of inventory accounting knowledge and the calculation of Cost of Goods Sold, considering that technological developments rely heavily on computer applications which often produce wrong outputs due to data input errors (Garbage In Garbage Out). Students at the Asih Lestari orphanage need this training in order to face the business world after graduating from high school.This PKM was carried out referring to letter no.004/YPA.AL/SK/II/2023 which was signed by the leadership of the Asih Lestari orphanage on Jl. Gardu no.1, Salembaran Jati, West Kosambi, Tangerang 152123. The aim of this PKM is expected to provide training in inventory accounting and HPP calculations to equip students when they enter the business world one day. This PKM activity was carried out on Monday 1 May 2023 at 08.00 – 13.00. The method used in this PKM is with tutorials and evaluation through short quizzes and questionnaires. The mandatory outputs of this PKM were presented in SERINA VI 2023. The results of this PKM were felt to be useful by students as seen from the results of the evaluation questionnaire which agreed and strongly agreed that 73% felt this material was really needed for learning in schools, 80% felt this material was needed for doing business in future, 66.66% stated that this material is interesting to study further. From the results of the questionnaire it was also seen that there was an increase in understanding of the material before and after the training and there was an increase in interest in the training material after the training. The conclusion of this PKM has been well implemented considering that the students of the Asih Lestari orphanage have become more understanding and more interested in this material.